THE RELEVANCE OF THE PHYTO-BEVERAGES PRODUCTION FOR THE PREVENTION OF CARDIOVASCULAR DISEASES - Babiy N.V.; Stepakova N.N.; Solovyova E.N. (Техника и технология пищевых производств)
Assortment policy in the food industry is largely determined by demographic changes, including an increase in the share of elderly and sick people. The body effects of various adverse factors, lead to changes in gene expression and gene structure that is accompanied by the disruption of protein synthesis and the body functions decrease. In modern conditions it is necessary to create high-quality and affordable products aimed at satisfying the population needs and having preventive properties. In this regard, the issues of scientifically rational use of wild medicinal and technical raw materials as a source of physiologically functional ingredients are of particular importance. The paper analyzes the main factors leading to premature aging. The ways to reduce dehydration in the elderly are suggested. The objects of study were wild-growing raw materials of Siberia and the Far East: the roots of rhodiola rosea, peppermint, hawthorn fruits, thoroughwax, golden clover, melilot drug, common origanum meeting the requirements of normative and technical documentation. The article presents the results of the quality indicators for 5 types of tea compositions. Analysis of physico-chemical indicators showed high antioxidant activity of the designed tea compositions. The clinical testing results of the phyto-beverages in the voluntary group of patients with ischemic heart disease and arterial hypertension are shown. The obtained results allow to consider the designed tea composition as a promising tool for the cardiovascular disease prevention efficiency control being based on subjective and objective data.